The Role of Motivation, Locus of Control and Financial Literacy on Women Investment Decisions Across Generations - Putri, Pranadya Tania; Simanjuntak, Megawati (Journal of Consumer Sciences, 2020)
This research gave attention to three factors that influence individuals in making investment decisions, motivation, locus of control, and financial literacy. This study generally aims to compare and analyze the effect of motivation, locus of control, and financial literacy on investment decisions on the families of the baby boomers generation, generation X, and generation Y. This study applied a direct interview method and uses a questionnaire as a data collection tool. Thirty housewives from each generation were interviewed. The results showed a significant difference in motivation and financia literacy between the three generations. The results also showed that all variables had a significant effect on investment decisions in each generation. Otherwise, overall, only the locus of control variable that has no significant effect on investment decisions. Based on this, the government together with investment service providers need to formulate an appropriate program. Apart from the education provided through educators, the program can also be provided with socialization and consultation services, either directly or indirectly. Development of supporting infrastructure and public access to financial institutions, products or services according to their needs and capacities also need attention.